(3GdfUQI dSjO GdYJQI aj MQH GdHUQIs - (3GdYcHQj, GdMGQKj, GdHZOGOj, GdcQNj, CHh YHO Gddg, GdTjN GdoepajO, eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe, J (B413s ((3Ydj Hf WGgQ Hf ejQ MGLs)
(3ChdgG (B:s
(3GdMeO ddg GdPj Vef GdfUQ dfG(B...(3hHYO CjOc Gddg HJhajbg SCdJ HCf ChQO dc PcQ GdGNJdGa Hjf Cgd GdbHdI aj MOjK GdaJfI HGdHUQI(B...s
(3BNQgG (B:s
(3hbO cGf aj efY GdMSf Ydjg GdSdGe Cf jOaf eY LOg Udi ajeG dG NdGa ajg Hjf GdYdeGA(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B696s
(3GdPQjYI(B:(3L(B24(3,U(B175(3,Qbe(B919s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds